The Effectiveness of Blended Learning in Increasing Prospective Physics Teacher Students’ Learning Motivation and Problem-Solving Ability - Ketut Suma; I.N.P Suwindra; Rai Sujanem (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
Advances in information technology have led to innovative learning methods that combine traditional and online learning, known as blended learning. This pre-experimental study aims to analyze the effectiveness of blended learning in increasing prospective physics teacher students’ learning motivation and problem-solving ability. There were 14 students who participated in this study. They were involved in 70% of face-to-face learning and 30% in online learning. The data of learning motivation were collected by the questioner and the data of problem-solving ability were collected by test. The research hypotheses were tested by non-parametric statistics, namely the sign test. The results of the study indicate that the pre-test score mean of learning motivation was 67.21 (SD= 5.45), which was in the medium level and the post-test score mean was 74.98 (SD=5.93), which was at a high level. The pre-test score means of problem-solving was 33. 43 (SD = 4.90) which was at a low-level and the post-test score mean was 63.54 (SD =2.35), which was at a moderate level. The one side sign test shows the calculated ZC= 3.43, which was higher than standard Z at a 5% significance level. The mean score of prospective physics teacher students’ learning motivation and problem-solving ability between before and after learning was significantly different. From this finding can be concluded that blended learning effective in increasing prospective physics teacher students’ learning motivation and problem-solving ability.